Cyber youth work in Hong Kong: Specific and yet the same. (September 2017) - Leung, Zeno CS; Wong, Stella SK; Lit, Siu-wai; Chan, Charlie; Cheung, Fabia; Wong, Pui-ling
Social media does not just lead to new ways of social participation; it creates new opportunities for serving difficult-to-reach groups in the community. This study examined the experiences and processes of a pioneering cyber youth work project working with young people involved in drug use and the sex trade in Hong Kong. A thematic analysis of online communication records and interviews of social workers and clients was conducted to determine the relating factors concerned, namely, 'social presence', 'autonomy and 'privacy', 'use of text and media', and 'time dimension'. The results suggest practice insights for youth workers.